Awesome Blossom a flower power book - Myracle, Lauren 1969- (Laura Ann); 1906-1998. 1958- 1947- (Sandra M.); 1957- (Margaret M.) (New York Amulet Books, 2013)
Fifth-grade best friends Katie-Rose, Milla, Yasaman, and Violet are determined to save a new student from Modessa's evil influence, but Katie-Rose is busy not flirting with Preston and all four are distracted by trying to organize Yasamin's sister's birthday party.
Keywords: Best friends -- Fiction; Friendship -- Fiction; Birthday parties -- Fiction; Schools -- Fiction; California